Association between obesity and chronic periodontitis: A nationwide population-based cohort study in Taiwan. Issue 41 (15th October 2021) - Chen, Tsung-Po; Yu, Hui-Chieh; Lin, Tai-Hsin; Wang, Yu-Hsun; Chang, Yu-Chao
Abstract : Abstract: Previous studies have suggested that obesity might be associated with chronic periodontitis (CP); however, no clear conclusions have been reached so far. In this retrospective cohort study, we aimed to investigate the association between obesity and CP by using a large population-based dataset in Taiwan. A population-based retrospective cohort study was conducted using the Longitudinal Health Insurance Database 2010 (LHID2010) derived from the National Health Insurance Research database in Taiwan, from 2000 to 2013. Obesity and non-obesity groups were matched with sex, age, urbanization level, socioeconomic status, and the related comorbidities by using the propensity score method at a 1:2 ratio. An obese cohort (n = 4140) and a non-obese cohort (n = 8280) were included in this study, with an average age of 41.7 ± 13.8 years and 42.0 ± 14.0 years, respectively. The risk of CP for the patients with obesity was 1.12-fold compared with those without obesity (hazard ratio, 1.12; 95% confidence interval, 1.01–1.25). In the subgroup analysis according to age and sex, the hazard ratio of CP were 1.98 (95% confidence interval, 1.22–3.22) in the subgroup of age equal to or older than 65 years. The risk of CP showed no difference between obesity and non-obesity groups in both sex. This population-based cohort study demonstrated that obesity was associated with the development of CP in Taiwan.